Seni Disiplin Tubuh dalam Perspektif Michel Foucault - Hardiansyah Hardiansyah (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Michen Foucault is a philosopher who also speaks about art. He explains about the essential of disciplining body. He argues that disciplining body is very an important art for human life. A modern individual is a discipline one, in which body is the most essential in the process. A discipline body will result responsible and dutiful individual. Discipline is doing all obligations based on his own will. It is not a forcing obligation from outsider. The development of mastery on one’s own body is a historical momentum where art training human body was introduced.